An Analysis of Indonesian EFL Teachers’ and Students’ Speech Acts in Teaching and Learning Process - Faiqotur Rizkiyah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This study is intended to describe, analyze and explain types of speech act produced by Indonesia EFL teachers and students in classroom. The subjects of this research are the teacher and the students. The data from this qualitative research was obtained from observation that were analyzed by three cyclical steps; data reduction, data display and conclusion. The study reveals that frequency of speech act occurred are representative (66, 7%), directive (23, 2 %), expressive (6, 56 %), and commusive (3, 54 %). The students produced more utterance (68, 25 %) than the teacher did (31, 75 %). The highest speech act production is representative which was produced by the students as the responds from the teacher’s direction. While the teacher tends to use directive speech act.